2013
DOI: 10.1590/s0100-29452013000300018
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de clones de bananeira 'Prata-Anã' (AAB) por meio de marcadores SSR

Abstract: Diversidade genética de 20 clones de 'Prata-Anã Gorutuba', quatro clones de 'Prata-Rio', quatro clones de 'Prata-Catarina' e as cultivares Caipira, Thap Maeo, Tropical, Maçã e Prata-Anã Comum foi avaliada por meio de marcadores moleculares Simple Sequence Repeats. De um total de 19 pares de primers SSRs utilizados, 57,8% deles amplificaram bandas polimórficas e distintas, 26,3% não produziram produtos específicos e 15,7% apresentaram falhas na amplificação de alguns indivíduos. O dendrograma indicou a formação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…These distances may be further explained by the presence of somaclonal variations in banana genotypes, providing high genetic diversity (Librelon et al, 2013). The study of genetic variability is of great importance when the objective is to improve a species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These distances may be further explained by the presence of somaclonal variations in banana genotypes, providing high genetic diversity (Librelon et al, 2013). The study of genetic variability is of great importance when the objective is to improve a species.…”
Section: Resultsmentioning
confidence: 99%
“…Working with microsatellites, also know as simple sequence repeats (SSR) markers in banana genotypes, Librelon et al (2013) concluded that these primers are able to discriminate clones of 'Prata-Anã Gorutuba' in relation to the banana cultivar Prata-Anã, indicating the existence of genetic variability among the studied material. Rout et al (2009) reported that inter simple sequence repeats (ISSR) markers were effective at demonstrating the genetic variability among banana cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Como todos os genótipos avaliados são da 'Prata-Anã', sugere-se, com a obtenção dessas distâncias, serem variantes somaclonais. Outros autores em caracterização de clones de bananeira também encontraram distâncias genéticas altas entre os genótipos avaliados, o que demonstra a existência de variações somaclonais (LIBRELON et al, 2013;RODRIGUES et al, 2012;GUBBUK et al, 2004). Em bananeira, ocorrem variações somaclonais em nível muito superior ao que se observa na maioria das outras culturas (provavelmente, devidas à instabilidade mitótica), principalmente em cultura de tecidos, que são também observadas no campo (SILVA et al, 2002), revelando então essa alta variabilidade genética entre elas.…”
Section: Resultsunclassified
“…Creste et al (2004) used SSR markers to study genetic diversity in 49 diploid accessions from the same germplasm bank as here and reported an average genetic similarity of 10%. Librelon et al (2013) examined genetic diversity of 'Prata-Anã' clones and observed that the 'Prata-Anã Gorutuba' clones and the cultivar 'Prata-Anã' showed similarity of 89%, with an average distance of 40.77% between the clones evaluated.…”
Section: Considering Microsatellite Markers As Co-dominantmentioning
confidence: 99%